Nurses Caring and Patientâs Satisfaction at Internal Medicine Unit of Dr. Soetomo Hospital, Surabaya - Hasanah, Nur; Indriatie, Indriatie; Padoli, Padoli; Saudah, Noer (Health Notions, 2017)
Patientâs satisfaction is crucial for a hospital, and nursing as an integral part of health care in hospitals also determine the level of patientâs satisfaction. At the order of the clinic nurses deal directly with the public as their client. A direct relationship between the nurse and the client need a behaviour that can be accepted by the whole society. Caring as one of the basic values of nursing, is a phenomenon that affects the way to think, feel and relate to others. This study aimed to analyze the relationship between the nurses caring with patientâs satisfaction by using cross sectional design. Population of this study was patients who were treated in Internal Medicine Unit of Dr. Soetomo Hospital in November 2015. The sample size was 75 people, who were selected  by simple random sampling technique. Data collection was done by filling out the questionnaire, then anayzed by using Chi-square test. Results showed 57.33% of the patients gave judgment of satisfactory to nurse caring behaviour and 42.67% gave a good assessment. 62.67% of the patients said they were satisfied with the caring services. There was a significant relationship between nurses caring with patient satisfaction.